PENGARUH ASPEK-ASPEK KINERJA LINGKUNGAN PERUSAHAAN TERHADAP HARGA SAHAM SYARIAH YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEX - Widya Sari (Jurusan Akuntansi Politeknik Negeri Bandung, 2018)
This research tried to relate the stock price changes with the orientation of the company in achieving maximum profit associated with corporate social responsibility. Beginning with the increasing demands and awareness of corporate social responsibility and the development of social accounting in Indonesia, there are several aspects that must be informed by the company to explain the impact of the company's activities on the economy, environment and social. These things are associated with market reactions and investor responses or potential investors in the capital market, then the research was conducted with the objective: “To Measure the Magnitude of The Effects of Environmental Performance Aspects on the Shariah Stock Price of the companies listed on the Jakarta Islamic Index”. The population in this research are the stock price of the companies listed on the Jakarta Islamic Index (JII) in Indonesia Stock Exchange (IDX). To analyze the data is used multiple regression analysis of panel data. The variables in this research consisted of independent variables, namely the environmental performance’s aspects as variable X, and dependent variable (Y) ie Shariah Stock Price. Based on the results of this research prove the existence of a strong relationship between independent variables simultaneously with the dependent variable, which means aspects of the Environmental Performance of the Company have a strong influence on the price of Islamic stocks in the Jakarta Islamic Index, if correlated together. Keywords: Environmental Performance, Stocks, Shariah.